Free radical scavenging profile and myeloperoxidase inhibition of extracts from antidiabetic plants: Bauhinia forficata and cissus sicyoides - Khalil, Najeh M. [UNESP]; Pepato, Maria T. [UNESP]; Brunetti, Iguatemy L. [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2008)
There is abundant evidence that reactive oxygen species are implicated in several physiological and pathological processes. To protect biological targets from oxidative damage, antioxidants must react with radicals and other reactive species faster than biological substrates do. The aim of the present study was to determine the in vitro antioxidant activity of aqueous extracts from leaves of Bauhinia forficata Link (Fabaceae - Caesalpinioideae) and Cissus sicyoides L. (Vitaceae) (two medicinal plants used popularly in the control of diabetes mellitus), using several different assay systems, namely, 2,2′-azino-bis(3- ethylbenzothiazoline-6-sulfonic acid) (ABTS) decolorization, superoxide anion radical (O2 •-) scavenging and myeloperoxidase (MPO) activity. In the ABTS assay for total antioxidant activity, B. forficata showed IC50 = 8.00±0.07 μg/mL, while C. sicyoides showed IC50 = 13.0±0.2 μg/mL. However, the extract of C. sicyoides had a stronger effect on O2 •- (IC50 = 60.0±2.3 μg/mL) than the extract of B. forficata (IC50 = 90.0±4.4 μg/mL). B. forficata also had a stronger inhibitory effect on MPO activity, as measured by guaiacol oxidation, than C. sicyoides. These results indicate that aqueous extracts of leaves of B. forficata and C. sicyoides are a potential source of natural antioxidants and may be helpful in the prevention of diabetic complications associated with oxidative stress.
Keywords: ABTS decolorization assay; Antioxidant activity; Superoxide anion scavenging activity